Longitudinal Impact of the Smoking Ban Legislation in Acute Coronary Syndrome Admissions. (7th February 2017) - Abreu, D.; Sousa, P.; Matias-Dias, C.; Pinto, F. J.
Abstract : Background and Purpose . The association between smoking and CV has been proved; however smoking is still the first preventable cause of death in the EU. We aim to evaluate the potential impact of the smoke ban on the number of ACS events in the Portuguese population. In addition, we evaluate the longitudinal effects of the smoking ban several years after its implementation. Methods . We analyzed the admission rate for ACS before and after the ban using data from hospital admission. Monthly crude rate was computed, using the Portuguese population as the denominator. Data concerning the proportion of smokers among ACS patients were obtained from the NRACS. Interrupted time series were used to assess changes over time. Results . A decline of −5.8% was found for ACS crude rate after the smoking ban. The decreasing trend was observed even after years since the law. The effect of the ban was higher in men and for people over 65 years. The most significant reduction of ACS rate was found in Lisbon. Conclusions . Our results suggest that smoking ban is related to a decline in ACS admissions, supporting the importance of smoke legislation as a public health measure, contributing to the reduction of ACS rate.